2015
DOI: 10.1016/s2095-3119(14)60943-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the C.–1 388 A>G polymorphism in chicken heat shock transcription factor 3 gene on heat tolerance

Abstract: Heat stress is one of the main factors that influence poultry production. Heat shock proteins (HSPs) are known to affect heat tolerance. The formation of HSPs is regulated by heat shock transcription factor 3 (HSF3) in chicken. A DNA pool was established for identifying single nucleotide polymorphisms (SNPs) of the chicken HSF3, and 13 SNPs were detected. The bioinformatic analysis showed that eight SNPs had the capacity to alter the transcription activity of HSF3. The dual luciferase report gene assay showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…respiration rates of the HS group were not significantly different from those of the NC and PF groups on day 42, suggesting that the broilers might exhibit an adaptation to heat acclimatization or heat tolerance. 20 The present results showed that heat exposure significantly decreased the ADFI compared with the NC group during days 28-35, 35-42 and 28-42. Moreover, the feed intakes of the HS and PF groups were similar, but the ADG and the feed conversation rate of the HS group were significantly lower than those of the wileyonlinelibrary.com/jsfa PF group, which indicated that high-temperature impairment on growth performance may exist as another mechanism besides the reduction in feed intake.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…respiration rates of the HS group were not significantly different from those of the NC and PF groups on day 42, suggesting that the broilers might exhibit an adaptation to heat acclimatization or heat tolerance. 20 The present results showed that heat exposure significantly decreased the ADFI compared with the NC group during days 28-35, 35-42 and 28-42. Moreover, the feed intakes of the HS and PF groups were similar, but the ADG and the feed conversation rate of the HS group were significantly lower than those of the wileyonlinelibrary.com/jsfa PF group, which indicated that high-temperature impairment on growth performance may exist as another mechanism besides the reduction in feed intake.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the respiration rates of heat‐exposed broilers were significantly elevated on days 28, 31 and 35, indicating that a chronic heat stress model was successfully established in this study . However, the respiration rates of the HS group were not significantly different from those of the NC and PF groups on day 42, suggesting that the broilers might exhibit an adaptation to heat acclimatization or heat tolerance …”
Section: Discussionmentioning
confidence: 74%
“…A high number of CD4+ T cells indicate a stronger immunity, which is not prone to infection, as the immune response is triggered swiftly by the invasion of the microorganisms. A high level of CD8+ T cells indicates a decrease in immunity and that the chicken requires a vaccine against pathogens (Zhang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + cells act as coordinators of the immune response by producing cytokines ( Arstila et al, 1994 ). In addition, a high number of CD4 + T cells indicates a stronger immunity as the immune response is triggered rapidly by the invasion of the microorganisms ( Zhang et al, 2015 ). Similarly, Joo et al (2022) reported that dietary NSMJ56 for 2 wk increased the percentage of CD4 + T cells in broiler chicks.…”
Section: Discussionmentioning
confidence: 99%